PEMBACAAN IDENTITAS KARTU BARCODE DENGAN MEMANFAATKAN SCANNER BARCODE UNTUK MEMASUKI RUANGAN PUSTAKA DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN BORLAND DELPHI 7.0 - Ruri Hartika Zain (Jurnal Processor, 2011)
A long growth of technology, specially computer area have given important role inhuman life. In this time computer do not only used to process just data, even computercan be used to control an system being based on electronics, so that useful power andability of computer system earn more optimal. Progress of computer area have colouredeach, every human life angle corner, good is company environment, white colars, otherenvironment and industry which exploit computerization system. This system is developedbasically is to facilitate work of human being. One of the its application example of byexploiting computer as controller of building security system, for example at room in aother institutions or building by using technology of barcode